Comparative study on heat extraction from Soultz-sous-Forêts geothermal field using supercritical carbon dioxide and water as the working fluid. (1st March 2023) - Singh, Mrityunjay; Mahmoodpour, Saeed; Ershadnia, Reza; Soltanian, Mohamad Reza; Sass, Ingo
Abstract: Energy extraction from the deep subsurface requires engineering using a working fluid circulation in well doublet. This study developed a field-scale hydro-thermal model to examine the heat extraction potential from Soultz-sous-Forêts with CO2 and water as the working fluid. A better understanding of the heat extraction mechanism is established by considering the reservoir response and the wellbore heat exchange. Sensitivity analyses are performed for different injection temperatures and flow rates for 50 years. Results show that the wellbore effect is multiple times higher than the reservoir response to the production temperature. Furthermore, lowering the injection temperature eventuates to a smaller temperature reduction at the subsurface, enhancing the overall heat extraction potential with a minor impact on thermal breakthrough. The cold region developed around the injection wellbore may affect the production fluid temperature due to its proximity to the production wellbore near the top of the reservoir. To reach higher heat extraction efficiency, it is essential to use sufficient wellbore spacing. CO2 can be used as working fluid for over 50 years as it does not show significant thermal breakthrough and temperature plume evolution in the reservoir under studied conditions. CO2 shows lower temperature reduction for all injection rates and temperatures for 50 years of operation. Highlights: CO2 is compared with water as the working fluid to extract geothermal energy from Soultz-sous-Forêts geothermal site. A finite element hydrothermal model is coupled with an analytical wellbore model for the fractured geothermal reservoir. Wellbore coupling has significant contribution on the final produced fluid temperature. CO2 shows lower temperature reduction in the faulted and the leakage zone for the entire operation.